Fotocatalisadores modificados baseados em PHI para oxidação do álcool alílico para ácido acrílico - Costa, Danielly Tamires da Silva (2024)
The production of plastics in the petrochemical industry significantly contributes to greenhouse gas (GHG) emissions, being responsible for 17% of global industrial emissions. In contrast, biomass, when used sustainably, is carbon-neutral because the carbon released during its combustion is used by plants in the photosynthesis process. Carbon nitrides are known as photocatalysts capable of promoting the oxidation of alcohols, including the conversion of aromatic alcohols to carboxylic acids under controlled conditions. However, the photooxidation of allyl alcohol to acrylic acid using carbon nitrides as catalysts has never been reported in the literature. In this study, we investigate the oxidation of allyl alcohol to produce acrylic acid using H-PHI, a crystalline carbon nitride with potential applications in oxidative reactions. The synthesis of the photocatalyst, based on crystalline carbon nitrides of the type (poly (heptazine imide) sodium (Na-PHI) followed procedures well reported in the literature. A series of catalysts with different degrees of protonation (H-PHI) were synthesized via controlled protonation of Na-PHI. The obtained catalysts were characterized by X-ray diffraction (XRD), high-resolution transmission electron microscopy (HR-TEM), Fourier transform infrared spectroscopy (FT-IR) and UV-spectroscopy. These catalysts were tested in photooxidation reactions of allyl alcohol to acrylic acid. Different variations in the reaction medium were explored, including solvent, amount of catalyst, and oxygen pressure as the oxidizing agent. These catalysts not only achieved high efficiency in conversion but also maintained excellent selectivity for the desired product. H- PHI catalysts proved to be more efficient than metal-doped PHI-based catalysts. Therefore, the results obtained demonstrate that protonated carbon nitrides (H-PHI) are a highly efficient and sustainable alternative to traditional catalysts, such as Mo8V2WOδ/SBA-15. Additionally, they are efficient at room temperature and low pressures. Our results indicate up to 100% selectivity for acrylic acid and 70% conversion using water as a solvent at room temperature.